2014
DOI: 10.1590/1807-3107bor-2014.vol28.0009
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal conditions of Colombian university students aged 16 to 35

Abstract: Periodontal conditions of Colombian university students aged 16 to 35Abstract: Epidemiological data on the periodontal health and oral hygiene practices of young individuals in Latin America are limited. This study was conducted in a sample of 355 first-year students randomly selected from 3,251 new students entering the largest university in Colombia. Participants received a periodontal examination and were interviewed about oral hygiene practices. Specifically, this study assessed the relationship between or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 16 publications
1
5
0
2
Order By: Relevance
“…Corroborating the deficiency in instituting this habit, a research in Nigeria showed that 48.6% of university students had never used dental floss (Folayan et al, 2013), similar to what was observed in Colombia (Marulanda et al, 2014). Low flossing habits were also observed in Lisbon (Fortes et al, 2016) and Brazil (Ferreira- Borges, Parry, & Barbor, 2017).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Corroborating the deficiency in instituting this habit, a research in Nigeria showed that 48.6% of university students had never used dental floss (Folayan et al, 2013), similar to what was observed in Colombia (Marulanda et al, 2014). Low flossing habits were also observed in Lisbon (Fortes et al, 2016) and Brazil (Ferreira- Borges, Parry, & Barbor, 2017).…”
Section: Discussionmentioning
confidence: 80%
“…Therefore, although studies suggest a good frequency of tooth brushing and use of toothbrush and toothpaste among academics of different nationalities (Marulanda, Coral, Sabogal, & Serrano, 2014;Peltzer & Pengpid, 2014;Halawany, Abraham, Jacob, & Al-Maflehi, 2015;Waheed, Saeed, & Jameel, 2017), the discrepancy between the self-perception of oral health and hygiene and the daily practice of dental cleaning may result from a deficiency in knowledge and adequate habits of oral health.…”
Section: Discussionmentioning
confidence: 99%
“…In Latin America, epidemiological data regarding oral health behavior are scarce, 21 and disclose only limited information on adult subjects. Furthermore, the studies are either limited to students, 22,23 teenagers 24 or patients, 25 or were conducted more than 15 years ago. 26 In this sense, studies performed in South America are of foremost interest.…”
Section: Introductionmentioning
confidence: 99%
“…En el estudio fueron incluidos treinta y ocho pacientes con un promedio de edad de El tercer estudio de salud buco-dental realizado en Colombia en el año 1998 encontró como aproximadamente el 70 % de la muestra de jóvenes entre los 20 y 24 años de edad presentaba sangrado gingival (4), estos resultados son compatibles con análisis a muestras de jóvenes universitarios de Bogotá donde se ha encontrado un Índice de Placa de O´Leary del 56 % y un porcentaje de hemorragia al sondaje de 37 % (20). Los valores del Índice de Placa de los estudiantes incluidos en el presente estudio son aún mayores, 72.6 %, y los de hemorragia al sondaje son similares a los descritos, 36.7 %; sin embargo los estudiantes no presentaron profundidades incrementadas al sondaje, ni una magnitud significativa de pérdida del nivel de inserción clínico, por lo cual el diagnóstico periodontal de ellos sería gingivitis.…”
Section: Resultados Descripción De La Muestra De Pacientesunclassified